Oxidized Haemoglobin–Driven Endothelial Dysfunction and Immune Cell Activation: Novel Therapeutic Targets for Atherosclerosis - Buttari, Brigitta; Profumo, Elisabetta; Businaro, Rita; Saso, Luciano; Capoano, Raffaele; Salvati, Bruno; Rigano, Rachele (Current Medicinal Chemistry, 2013)
Atherosclerosis is a chronic inflammatory disease of the arterial wall characterized by endothelial dysfunction, and in which innate and adaptive immune responses have a crucial role. Autoimmune reactions against several self molecules and modified self molecules have been identified in patients with atherosclerotic disease. Oxidative stress, increasingly reported in these patients is the major event causing protein structural modifications, thus inducing the appearance of neo/cryptic epitopes. Following intraplaque haemorrhage large amounts of cell-free haemoglobin (Hb) accumulate within atheroma, due to its impaired clearance by the haptoglobin-CD163 scavenging system. The pro-oxidative intraplaque microenvironment may induce Hb structural changes, thus generating neo/cryptic autoantigenic epitopes and rendering the oxidized self molecule as a dangerous signal for both immune and endothelial cells. In this review, we will present the most relevant information on Hb as a candidate self antigen involved in the pathogenesis of atherosclerotic disease and on its ability to trigger signals that drive endothelial dysfunction and immune cell activation. On these grounds, we will also discuss how these new paradigms may lead to novel therapeutic targets for cardiovascular diseases.
Keywords: haptoglobin